2008
DOI: 10.1242/dev.029736
|View full text |Cite
|
Sign up to set email alerts
|

Attribution of vascular phenotypes of the murine Egfl7 locus to the microRNA miR-126

Abstract: Intronic microRNAs have been proposed to complicate the design and interpretation of mouse knockout studies. The endothelialexpressed Egfl7/miR-126 locus contains miR-126 within Egfl7 intron 7, and angiogenesis deficits have been previously ascribed to Egfl7 gene-trap and lacZ knock-in mice. Surprisingly, selectively floxed Egfl7 ⌬ and miR-126 ⌬ alleles revealed that Egfl7 ⌬/⌬ mice were phenotypically normal, whereas miR-126 ⌬/⌬ mice bearing a 289-nt microdeletion recapitulated previously described Egfl7 embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
326
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(337 citation statements)
references
References 25 publications
7
326
1
3
Order By: Relevance
“…Conditional deletion of VCAM1 or α4-integrin in hematopoietic, stromal and endothelial cells by a Tie2-driven cre transgene increased the release of hematopoietic progenitors from the bone marrow into the circulation. 37,38 Antibodies to VCAM1, to α4 integrin, 22,24,25 and BIO5192, a small molecule inhibitor of VLA4 (α4b1 integrin) binding to VCAM1, 21 promoted the mobilization of HSPC in mice and/or humans, providing strong evidence that disruption of an interaction between VLA4 and VCAM1 promotes HSPC mobilization. 37 However, a link between G-CSF mobilization of HSPC and modulation of VCAM1/VLA4 in the bone marrow has previously been missing.…”
Section: Discussionmentioning
confidence: 99%
“…Conditional deletion of VCAM1 or α4-integrin in hematopoietic, stromal and endothelial cells by a Tie2-driven cre transgene increased the release of hematopoietic progenitors from the bone marrow into the circulation. 37,38 Antibodies to VCAM1, to α4 integrin, 22,24,25 and BIO5192, a small molecule inhibitor of VLA4 (α4b1 integrin) binding to VCAM1, 21 promoted the mobilization of HSPC in mice and/or humans, providing strong evidence that disruption of an interaction between VLA4 and VCAM1 promotes HSPC mobilization. 37 However, a link between G-CSF mobilization of HSPC and modulation of VCAM1/VLA4 in the bone marrow has previously been missing.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have also demonstrated that miR-126 has roles in regulating adhesion molecule expression (Harris et al, 2008), providing additional control of vascular inflammation (Harris et al, 2008), regulating the VEGF/PI3K/AKT signaling pathway (Hu et al, 2010), regulating the translation and invasiveness of vascular endothelial cell sprouting (Musiyenko et al, 2008), and governing the integrity and angiogenesis of the vasculature (Kuhnert et al, 2008;Wang et al, 2008b). Using MTT assays, our research showed that the SR of Siha-miR-126 mimic was significantly reduced compared to that of control cells and that the differences between the 2 cell groups increased over time.…”
Section: Discussionmentioning
confidence: 99%
“…Human Y79 retinoblastoma-derived cells (4 × 10 5 cells per well; ATCC) were transfected with Lipofectamine 2000 (Invitrogen) in 12-well plates with each of the six miRs from the miR-17 family. Distinct time points (3,6,12, and 24 h) as well as various miR concentrations (3, 10, and 30 nM) were tested to evaluate the effects of miR transfection on the levels of HIF1A and VEGFA expression relative to negative controls. Off-target effects and specificity of the selected miRs were further evaluated using the nontargeted, Cy5-labeled control 1 miR (Ambion) at the same time points and concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a large body of literature identified and confirmed a number of miRs that regulate angiogenesis (1)(2)(3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%